Determination of an Optimum Premium Paid in M&A Transactions in Oil and Gas Section - Варвара Вадимовна Назарова; Оксана Руслановна Шевякина (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2015)
Varvara Vadimovna Nazarova - SPbHE&M, St. Petersburg.E-mail: nvarvara@list.ruOksana Ruslanovna Shevyakina - National Research University "Higher School of Economics", St. Petersburg.E-mail: shevyakina.oksana@mail.ruMergers and acquisitions are an important part of the economy of any country. In difficult circumstances companies increasingly difficult to carry out a successful deal M & A. It is necessary to take into account the large number of nuances in preparation for the transaction, which have a direct impact on the quality of its implementation. One of the most important nuances is to determine the optimal value of the premium in the transaction M & A. This issue contains a very sound basis for understanding the true direction of the transaction M & A, since it affects, it is advantageous to be performed dealings, whether a positive synergistic effect and many other important aspects. Generally speaking, if a company - not just the absorber actually calculate the correct value of the premium, it may be at a loss for a deal giving a greater value than it receives from the profit.The thematic justification of this study is that at the planning stage of M & A transactions is necessary to determine the optimum value and correct premium, for both the seller and the buyer. For the company - seller, it becomes an important aspect of the deal to receive an amount not less than the value of the part of the assets which he sells. For the buyer it is important not to overpay for the deal because a too high premium guarantee an absent of future synergies, and possibly negative outcome for the company until its bankruptcy.The purpose of this article focuses on the determination the formation of the optimal value premium in M & A transactions, in terms of the oil and gas sector, through the identification of financial and non-financial factors that have a direct impact on the premium rate.The object of this study is M & A transactions in the oil and gas industry. Item - premiums paid during the M & A transactions in the oil and gas sector by the buyer to the seller.In consequence of  research, the regression model was developed. This model explaining the dependence of the acquisition premium value’s of  certain financial and non-financial factors: the market capitalization has a positive effect on the formation of the value of the premium; operating profit target and the number of outstanding shares are negative depending on the size of the premium; at the conglomerate and vertical (vertical - slightly below) mergers the premium size  is significantly higher than the horizontal merger; information asymmetry has a positive effect on the premium; cross-border transaction type also has a positive effect on the value of the premium.The final model has a strong explanatory power.It is necessary to be noted that not the only financial data of the financial performance of the target is influenced on the amount of premiums but some related factors which may be used in calculating each other in this type of research.